2006
DOI: 10.1038/ncb1421
|View full text |Cite
|
Sign up to set email alerts
|

Processive bidirectional motion of dynein–dynactin complexes in vitro

Abstract: Cytoplasmic dynein is the primary molecular motor responsible for transport of vesicles, organelles, proteins and RNA cargoes from the periphery of the cell towards the nucleus along the microtubule cytoskeleton of eukaryotic cells. Dynactin, a large multi-subunit activator of dynein, docks cargo to the motor and may enhance dynein processivity. Here, we show that individual fluorescently labelled dynein-dynactin complexes exhibit bidirectional and processive motility towards both the plus and minus ends of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
309
5
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(343 citation statements)
references
References 40 publications
27
309
5
2
Order By: Relevance
“…The motile behaviour of mammalian dynein has been studied using complexes purified from brain (Mallik et al , 2005; Ross et al , 2006; Miura et al , 2010; Ori‐McKenney et al , 2010; Walter et al , 2010) and tissue culture cells (Ichikawa et al , 2011), as well as complexes reconstituted from individual, recombinant components (Trokter et al , 2012). Movement of individual mammalian dynein complexes has been assayed by adhering the motor to beads (King & Schroer, 2000; Mallik et al , 2005; Walter et al , 2010), labelling accessory proteins (Ross et al , 2006; Miura et al , 2010) or by GFP tagging of the motor (Trokter et al , 2012). The extent to which individual dynein complexes can take multiple successive steps without detaching from the microtubule, a behaviour termed processivity, varied in these studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motile behaviour of mammalian dynein has been studied using complexes purified from brain (Mallik et al , 2005; Ross et al , 2006; Miura et al , 2010; Ori‐McKenney et al , 2010; Walter et al , 2010) and tissue culture cells (Ichikawa et al , 2011), as well as complexes reconstituted from individual, recombinant components (Trokter et al , 2012). Movement of individual mammalian dynein complexes has been assayed by adhering the motor to beads (King & Schroer, 2000; Mallik et al , 2005; Walter et al , 2010), labelling accessory proteins (Ross et al , 2006; Miura et al , 2010) or by GFP tagging of the motor (Trokter et al , 2012). The extent to which individual dynein complexes can take multiple successive steps without detaching from the microtubule, a behaviour termed processivity, varied in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…The extent to which individual dynein complexes can take multiple successive steps without detaching from the microtubule, a behaviour termed processivity, varied in these studies. Some groups reported a subset of dyneins undergoing processive movements with an average run length of approximately 0.7–1 μm (King & Schroer, 2000; Mallik et al , 2005; Culver‐Hanlon et al , 2006; Ross et al , 2006), whereas others documented substantially shorter excursions (Ori‐McKenney et al , 2010). Other studies reported no measurably processive movement (Miura et al , 2010; Trokter et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The critical dynactin subunit for plus‐end tracking is p150 Glued (called p150 here). Its N‐terminal CAP‐Gly domain protrudes from the shoulder of the dynactin complex (Chowdhury et al , 2015; Urnavicius et al , 2015) and binds directly to microtubules (Culver‐Hanlon et al , 2006; Peris et al , 1998; Ross et al , 2006), as well as to EBs (Honnappa et al , 2006). In vitro reconstitution experiments with a p150 fragment showed that the p150 CAP‐Gly domain and the first coiled‐coil of p150, which interacts with the intermediate chain of the dynein complex (Karki & Holzbaur, 1995; Vaughan & Vallee, 1995; King et al , 2003), were sufficient for mediating EB‐dependent end tracking of the human dynein complex (Duellberg et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In experiments on dynein alone, is seen to move progressively, however it is a simplification of what is seen in experiments on the dynein moving cargo. Experiments do show cargos within a cell being moved in the direction of the nucleus over time, however there are also pauses in movement and the cargo can travel backwards or move in a direction which is not solely radial [21,12,42,46]. Currently, the available experimental data does not show how the dynein itself is behaving at these times, as we only see the position of the endosome.…”
Section: Variation Of Parametersmentioning
confidence: 78%
“…Currently, the available experimental data does not show how the dynein itself is behaving at these times, as we only see the position of the endosome. The pauses and retrograde transport may be a result of the action of kinesins on the cargo, either in a tug-of-war scenario, dynein may occasionally fall off a microtubule, or simply become inhibited by a crowded cytoplasm [1,21,38,42,48]. In addition, non-radial movement, could also be a result of dynein being detached from the cargo or the microtubule.…”
Section: Variation Of Parametersmentioning
confidence: 99%